Adaptation and validation of home-based involvement scale in the Indonesian Version - Nur Ainy Fardana; Novia Solichah (Cogent Psychology, 2025)
This study focuses on the adaptation and validation of the Home-Based Involvement Scale, originally developed by PIRLS, to measure parental involvement in early literacy within an Indonesian context. Following the International Test Commission’s guidelines, the adaptation process included translation, cultural adaptation, and empirical testing. Data were collected from 987 parents, with 593 valid responses analyzed after excluding incomplete data. The participants’ ages ranged from 21 to 78 years (M = 35.93, SD = 7.6). The initial CFA supported a unidimensional model with adequate fit indices; however, one item demonstrated a low factor loading (0.353) and was subsequently removed. A revised 8-item model showed improved psychometric properties, including better factor loadings (0.576–0.683), increased Average Variance Extracted (AVE = 0.523), and high internal consistency (CR = 0.787; α = 0.784). The results suggest that the Indonesian version of the Home-Based Involvement Scale is a reliable and effective tool for measuring parental involvement in early literacy. Future research is encouraged to explore the scale’s applicability in various demographic groups and its potential use in longitudinal studies to enhance its generalizability.